(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article presents information on the influence of active temperatures (above 5°C) occurring during different sowing periods of early carrots on the growth and development stages of the crop. The highest sums of active temperatures during the period from seed germination to technical maturity of root crops were recorded in the sowing periods of April 20 and May 1, amounting to 2720–2816°C. The lowest sum of active temperatures was observed in the first sowing period (April 1), reaching 1970°C.